Techno-economic analysis of forward osmosis pre-concentration before an anaerobic membrane bioreactor: Impact of draw solute and membrane material. (1st July 2022) - Vinardell, Sergi; Blandin, Gaetan; Ferrari, Federico; Lesage, Geoffroy; Mata-Alvarez, Joan; Dosta, Joan; Astals, Sergi
Abstract: This research investigated the impact of draw solute and membrane material on the economic balance of a forward osmosis (FO) system pre-concentrating municipal sewage prior to an anaerobic membrane bioreactor (AnMBR). Eight and three different draw solutes were evaluated for cellulose triacetate (CTA) and polyamide thin film composite (TFC) membranes, respectively. The material of the FO membrane was a key economic driver since the net cost of TFC membrane was substantially lower than the CTA membrane. The draw solute had a moderate impact on the economic balance. The most economically favourable draw solutes were sodium acetate and calcium chloride for the CTA membrane and magnesium chloride for the TFC membrane. The FO + AnMBR performance was modelled for both FO membrane materials and each draw solute considering three FO recoveries (50, 80 and 90%). The estimated COD removal efficiency of the AnMBR was similar regardless of the draw solute and FO membrane material. However, the COD and draw solute concentrations in the permeate and digestate increased as the FO recovery increased. These results highlight that FO membranes with high permselectivity are needed to improve the economic balance of mainstream AnMBR and to ensure the quality of the permeate and digestate. Highlights: The techno-economic analysis of combining FO and AnMBR technologies was conducted. The FO membrane material largely impacted the economic balance of the system. The draw solute did not have a high impact on the economic balance of the system. FO installation and draw solution were the most important cost contributors. Organic and draw solute concentrations in AnMBR permeate increased with FO recovery.